CFD-Based Comparative Study of Axe Bow and Bulbous Bow Designs for Corvette Warship Deployment in Natuna Waters - Yeddid Yonatan Eka Darma; Reyhan Arfananda Sugiarto; Achdri Fauzi Nugraha Oloan; Fajri Narotama (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The Natuna Sea is considered a prime maritime area for Indonesia, bearing strategic and defense significance, besides its turbulent sea conditions demand warships to adopt or be provided with efficient and stable hull forms. Thus, this study is intended to investigate the most appropriate bow designs for a corvette warship operating in the Natuna region. Three types of bow are compared: a conventional V-hull, sloped bow, bulbous bow and axe bow. Comparison through Computational Fluid Dynamics (CFD) simulation, validated with Holtrop and Savitsky empirical methods, at the speed of 30 knots. Principal dimensions of the corvette were obtained through regression analysis from 20 other warships that belong to the same class. Results reveal that the axe bow has the smallest resistance, that is, 365.18 kN from Holtrop method and 374.27 kN from CFD in contrast to 384.43 kN owing to conventional bow design. It also fulfills all criteria of operation performance and fuel efficiency. Hence, it is considered the best alternative for corvette deployment into the Natuna Sea.